mRNA vaccines encoding membrane-anchored RBDs of SARS-CoV-2 mutants induce strong humoral responses and can overcome immune imprinting - Hareth A. Al-Wassiti; Stewart A. Fabb; Samantha L. Grimley; Ruby Kochappan; Joan K. Ho; Chinn Yi Wong; Chee Wah Tan; Thomas J. Payne; Asuka Takanashi; Chee Leng Lee; Rekha Shandre Mugan; Horatio Sicilia; et al. (Molecular Therapy: Methods & Clinical Development)
We investigated mRNA vaccines encoding a membrane-anchored receptor-binding domain (RBD), each a fusion of a variant RBD, the transmembrane (TM) and cytoplasmic tail fragments of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein. In naive mice, RBD-TM mRNA vaccines against SARS-CoV-2 variants induced strong humoral responses against the target RBD. Multiplex surrogate viral neutralization (sVNT) assays revealed broad neutralizing activity against a range of variant RBDs. In the setting of a heterologous boost, against the background of exposure to ancestral whole-spike vaccines, sVNT studies suggested that BA.1 and BA.5 RBD-TM vaccines had the potential to overcome the detrimental effects of immune imprinting. A subsequent heterologous boost study using XBB.1.5 booster vaccines was evaluated using both sVNT and authentic virus neutralization. Geometric mean XBB.1.5 neutralization values after third-dose RBD-TM or whole-spike XBB.1.5 booster vaccines were compared with those after a third dose of ancestral spike booster vaccine. Fold-improvement over ancestral vaccine was just 1.3 for the whole-spike XBB.1.5 vaccine, similar to data published using human serum samples. In contrast, the fold-improvement achieved by the RBD-TM XBB.1.5 vaccine was 16.3, indicating that the RBD-TM vaccine induced the production of antibodies that neutralize the XBB.1.5 variant despite previous exposure to ancestral spike protein.